Shifting the management model of Brazilian health services: perceptions of major stakeholders on the participation of the private sector in public hospital administration - Bárbara Bulhões; Hugo Bellas; Rodrigo Arcuri; Paulo Victor Rodrigues de Carvalho; Alessandro Jatobá (Elsevier, 2022)
In Brazil, public hospitals are managed according to several different models. The participation of private or third-sector organizations has been growing in a significant manner, especially in the past decade. The present study explores the perception of public administrators and health councilors on the main aspects of outsourcing the management of public health services to the private sector. The study shows that the main disadvantages are related to the reduction of the State's role as regulator, making it more difficult to size services up according to the demands of the population. Among the main advantages pointed out are contributions to reduce bureaucracy in the administration and more freedom for the management of physical, financial, and human resources. The present study contributes to transcend the political-ideological discussion on private sector participation in the management of public and universal constitutionally guaranteed services, presenting the point of view of administrators in Brazil, not very explored in recent literature.